Complete treatment experience on psoriasis patients with secukinumab in real practice in Krasnodar region - L. S. Kruglova; A. A. Khotko (Лечащий Врач, 2021)
The article presents modern data on complete treatment of psoriasis with genetically engineered biological preparations in Krasnodar region. Clinical cases of successful treatment of patients with psoriasis vulgaris and nail psoriasis with secukinumab are presented in this publication.